PUBLIC RELATIONS DIVISION TOBACCO INSTITUTE COMMUNICATIONS MISSION STATEMENT (Tufts Archival Research Center, 2007)
Communications mission statement from the public relations division of the Tobacco Institute. Provides a general background on the responsibilities of the Tobacco Institute and then goes into detail regarding each responsibility. Lists the prior actions taken, the strategies for future actions and the official position of the TI on each issue.